2008
DOI: 10.1161/atvbaha.107.159392
|View full text |Cite|
|
Sign up to set email alerts
|

Sphingosine-1-Phosphate Receptor Subtypes Differentially Regulate Smooth Muscle Cell Phenotype

Abstract: Objective-The role of sphingosine-1-phosphate (S1P) receptors in acute vascular injury and smooth muscle cell (SMC) phenotypic modulation is not completely resolved. Methods and Results-S1P receptor antagonists were used to test the hypothesis that specific S1P receptor subtypes differentially regulate SMC phenotypic modulation. In response to acute balloon injury of the rat carotid artery, S1P1/S1P3 receptor mRNA levels were transiently increased at 48 hours whereas S1P2 receptor expression was decreased. S1P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
103
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(109 citation statements)
references
References 40 publications
6
103
0
Order By: Relevance
“…Additionally, pharmacological inhibition of S1P 1 and S1P 3 prevented S1P-induced SMC proliferation and potentiated expression of genes that define the contractile phenotype. 25 In the studies presented herein, pharmacological stimulation of S1P 1 and S1P 3 enhanced neovascularization and vessel maintenance, processes that require SMC proliferation, suggesting a potential phenotypic switch to the synthetic phenotype. Thus, manipulating the phenotypic modulation of vascular SMCs pharmacologically by strategically targeting known S1P receptor expression patterns could provide new avenues for growth of microvascular networks.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Additionally, pharmacological inhibition of S1P 1 and S1P 3 prevented S1P-induced SMC proliferation and potentiated expression of genes that define the contractile phenotype. 25 In the studies presented herein, pharmacological stimulation of S1P 1 and S1P 3 enhanced neovascularization and vessel maintenance, processes that require SMC proliferation, suggesting a potential phenotypic switch to the synthetic phenotype. Thus, manipulating the phenotypic modulation of vascular SMCs pharmacologically by strategically targeting known S1P receptor expression patterns could provide new avenues for growth of microvascular networks.…”
Section: Discussionmentioning
confidence: 61%
“…S1P 2 -induced diminution of SMC proliferation is consistent with the published results of others, who showed that VPC44116 significantly reduced neointimal hyperplasia (SMC proliferation) after acute balloon injury of the rat carotid artery. 25 Selective activation of S1P 2 by S1P likely results in SMC phenotypic modulation to the contractile phenotype, with increased expression of SMA or other SMC differentiation marker genes.…”
mentioning
confidence: 99%
“…Interestingly, a recent study showed that S1P 1 /S1P 3 receptors promote proliferative responses of smooth muscle cells in balloon injury models in vivo and in cultured cells in vitro, whereas S1P 2 receptors antagonize these responses. 63 However, the roles of S1P 1 in constriction responses of VSMCs remain less completely characterized. In addition, the activation of S1P receptors induces constriction responses in smooth muscle cell of non-vascular origin.…”
Section: Sphingosine-1-phosphate Receptors In Vascular Smooth Muscle mentioning
confidence: 99%
“…Prior evidence supporting the positive role of S1P 1 and S1P 3 in maintaining vascular cell proliferative=migratory phenotypes 14,15 guided our choice to evaluate the ability of two S1P receptor-targeted compounds, FTY720 (S1P 1 , S1P 3 agonist) and VPC01091 (S1P 1 agonist, S1P 3 antagonist), to enhance neovascularization, smooth muscle cell recruitment, and new bone formation within a cranial defect model. This new study demonstrates that by using receptor-selective compounds we can accurately amplify the therapeutic effects of endogenous S1P and subsequently improve both microvascular remodeling and osseous tissue growth in vivo to regenerate and restore tissue function.…”
Section: Introductionmentioning
confidence: 99%